XML for the World Wide Web / Visual QuickStart Guide - Castro Elizabeth (Peachpit Press, 2001)
Introduction, XML, Writing XML, DTDs, Creating a DTD, Defining Elements and Attributes in a DTD, Entities and Notations in DTDs, XML Schema and Namespaces, XML Schema, Defining Simple Types, Defining Complex Types, Using Namespaces in XML. Namespaces and Schemas and Validation, XSLT and XPath, XSLT, XPath: Patterns and Expressions, Test Expressions and Functions, Cascading Style Sheets, Setting up CSS, Layout with CSS, Formatting Text with CSS, XLink and XPointer, Appendices, Index and Colophon and Note.